New opportunities in treatment of patients with discirculatory encephalopathy: emphasis on nervous growth factor - Mishchenko, Tamara S.; Sokolik, Viktoriya V.; Mishchenko, Vladislav M.; Darii, Ivan V. (Psychiatry, Neurology and Medical Psychology, 2020)
The paper presents the results of research on the role of neuronal growth factors in the development and progression of cognitive and psychoemotional disorders. Peculiarities of Bacopa Monier and Ginkgo Biloba influence on structural and functional changes of the brain in the experiment and in certain groups of patients are shown. The results of treatment with phytocomplex (FC) Memostim® (fixed combination of Bacopa Monier - 150 mg and Ginkgo Biloba - 120 mg) of 30 patients with DE II grade due to atherosclerosis and hypertension are described. The control group consisted of 30 patients with grade II DE who were not prescribed FC Memostim®. After 3 months of treatment with FC Memostim®, a decrease in the frequency and severity of cephalic, vestibulo-atactic and asthenic syndromes was observed in patients. There was a significant improvement in cognitive functions (on the MoSA scale) and psycho-emotional state of patients. There was a significant improvement in the calculated operations and attention (by 22% relative to baseline, p <0.05) and the overall score on the test (+ 8%, p> 0.05). The general tendency to improve visual-constructive functions, memory, speech, executive functions, abstract thinking and orientation has been identified. Similar results of the effect of FC Memostim® on cognitive functions were obtained from the FAB questionnaire. According to the results of the survey of patients on the scale of quality of life, a significant positive dynamics of the integrative index (statistically significant increase by 31%), index of psychological well-being (increase by 32%), self-satisfaction (by 28%), indicators of physical well-being (by 18%) after 3 months of treatment with FC Memostim®. The level of neuronal growth factor (β-NGF) increased statistically significantly (by 67%). The analysis of the obtained data testifies to the effectiveness and safety of FC Memostim® in the treatment of patients with DE. Thus, the obtained data demonstrate the profound effect of FC Memostim® on the symptoms of cognitive and psychoemotional disorders in patients with DE, which is associated with an increase in NGF levels on the background of the course.